Alexithymia among alcohol dependent patients and its relationship with depression, anxiety and personality disorders - Evren, E. Cüneyt; Eken, Bahar; Çakmak, Duran (Journal of Dependence, 2003)
Objective: Aim of this study was to evaluate the alexithymia and its relationship with depression, anxiety and personality disorders alcohol dependent patients.Method: The study sample consisted of 105 male alcoholics who fulfilled DSM-IV criteria of alcohol dependence and finished detoxification process. A semistructured socio-demographic form, all the modules of Structured Clinical Interview for DSM-IV (SCID-I, SCID-II) Hamilton Depression Rating Scale (HDRS), Hamilton Anxiety Scale (HAM-A) and Toronto Alexithymia Scale (TAS-26) were applied.Results: The ratio of being alexithymic, based on TAS-26, was 36.2% in alcohol dependent patients. The mean age of starting to use alcohol was lower in alexithymic group than non alexithymic group. There were no differences between groups according to diagnosis of personality disorder. The mean score of HDRS and HAM-A were higher in alexithymic group. There was TAS-26, HDRS HAM-A total scores, and subscales of HAM-A there were positive correlations among, while there was no correlation between TAS-26 and total score of MAST.Conclusion: The high ratio of alexithymia found in this study suggests that it is important to diagnose alexithymia in alcohol dependents. There was no relationship between alexithymia and personality disorders among alcohol dependents in our study sample. This finding supports the notion that alexithymia is a personality trait.
Keywords: Alcohol dependence; alexitymia; depression; anxiety; personality disorder